Empowering Women: The Effect of Schooling on Young Women's Knowledge and Use of Contraception - Mabel Andalón; Jenny Williams; Michael Grossman (Institute for the Study of Labor (IZA), 2014)
Large differences in fertility between women with high and low levels of education suggest that schooling may have a direct impact on knowledge and use of contraception. We investigate this issue using information on women in Mexico. In order to identify the causal effect of schooling, we exploit temporal and geographic variation in the number of lower secondary schools built following the extension of compulsory education in Mexico from 6th to 9th grade in 1993. We show that raising females' schooling beyond 6th grade increases their knowledge of contraception during their reproductive years and increases their propensity to use contraception at sexual debut. This indicates that the impact of schooling on women's wellbeing extends beyond improved labour market outcomes and includes greater autonomy over their fertility.
Keywords: I10; I18; I25; 330; schooling; empowerment; contraception; knowledge; natural experiment; Mexico